1997
DOI: 10.1097/00005373-199712000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Quantity of Skeletal Injury on Mortality and Pulmonary Morbidity

Abstract: The combination of skeletal and chest injuries does not seem to amplify the pulmonary morbidity and mortality compared with chest injury alone. The quantity of the skeletal injury and the time to fixation of structures affecting mobilization seem to have an effect on pulmonary morbidity and mortality. Better scientific studies on the effects of skeletal injury and timing to fixation in relation to pulmonary morbidity and mortality are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Comparison with existing literature remains difficult since previous investigations only comprise small cohorts. [11][12][13] Also, the interpretation of data, particularly concerning surgical treatment must consider that isolated injuries and fractures of an extremity represent a different entity compared to the same injury in a multiple trauma patient. Furthermore, in our analysis extremity fractures might partially have remained classified under ''conservative treatment'' just because patients never reached surgery, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison with existing literature remains difficult since previous investigations only comprise small cohorts. [11][12][13] Also, the interpretation of data, particularly concerning surgical treatment must consider that isolated injuries and fractures of an extremity represent a different entity compared to the same injury in a multiple trauma patient. Furthermore, in our analysis extremity fractures might partially have remained classified under ''conservative treatment'' just because patients never reached surgery, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with isolated skeletal injury showed a lower mortality than those with isolated chest trauma or combined chest and skeletal trauma. 11 Probst et al examined the incidence and significance of foot and ankle injuries in polytrauma patients and found that patients without foot and ankle injuries had a significantly higher injury severity of the head and a significantly higher mortality in contrast to patients with foot and ankle injuries. 12 Weening et al assessed the incidence and mortality of polytrauma patients with and without scapular fractures 13 and described that the presence of a scapular fracture was associated with a mortality reduction of 44%.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with serious abdominal injuries, undergoing delayed treatment was associated with an estimated mortality risk that was 36% that of early treatment, and this relative risk was significantly lower than that for patients without such injuries. Several studies have shown abdominal injuries to be an important risk factor for mortality and morbidity in the patient with multisystem trauma 54,55 . Schulman et al 56 reported on a series of patients with blunt trauma undergoing a standardized resuscitation protocol and found only Injury Severity Score, abdominal injury (Abbreviated Injury Score, ‡3), and extremity and osseous pelvic injury (Abbreviated Injury Score, ‡3) to be significantly associated with prolonged occult hypoperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, this risk is increased to a much greater extent by the presence of a concomitant chest or head injury, hypovolaemia or the requirement for repeated blood transfusion. 34,[79][80][81][82] The wisdom of attempting early definitive surgery for all patients with fractures has been questioned in recent years. Most of the debate has centred on whether there are particular anatomical and physiological patterns of injury which may benefit from either a delay in a definitive operation or the use of alternative techniques to that of reamed nailing.…”
Section: Epidemiology Of Post-traumatic Respiratory Compromisementioning
confidence: 99%
“…Similar modifications to the management of the fracture to those described above have been suggested to reduce the extent of FE. The available clinical evidence, however, suggests that it is the chest injury which primarily determines whether the patient develops ARDS and not the femoral fracture, 67,68,74,82,93,95,105,106 since the risk of this complication in patients with an injured chest remains the same, irrespective of whether or not they have an associated femoral fracture (Figs 3a and 3b). This is substantiated by the absence of a significant difference in the risk of ARDS when comparing patients with chest injury alone with those who also have femoral fractures (Fig.…”
Section: 84-86mentioning
confidence: 99%